Attachment, loss, and related challenges in migration. (October 2022) - Venta, Amanda; Cuervo, Maria
Abstract: Attachment theory—built on the knowledge that infants have an innate need to form an attachment bond with a caregiver and that separation from or loss of that caregiver has a lasting impact on the child's development—is a useful lens through which to examine the consequences of family separation due to migration. The aim of this review was to highlight the impacts of separation due to migration on children's attachment security and psychosocial outcomes to illustrate that family separation—regardless of whether is it "chosen" by a family who sees no other path towards safety or prosperity or inflicted by legal policies associated with immigration, detention, and deportation—negatively affects children's attachment security with serious consequences for their well-being.